Seroepidemiological analysis and literature review of the prevalence of Epstein‐Barr virus and herpesvirus infections in pediatric cases with non‐Hodgkin lymphoma in Central Europe. Issue 7 (12th April 2019) - Vaillant, Vera; Reiter, Alfred; Zimmermann, Martin; Wagner, Hans‐Joachim
Abstract: Background: Epstein‐Barr virus (EBV) is linked to a variety of malignancies; most endemic Burkitt lymphoma (BL) harbor EBV, whereas only a subset of the cases of sporadic BL is EBV positive. Procedure: We retrospectively determined the herpesvirus seroprevalence at the time of diagnosis in pediatric non‐Hodgkin lymphoma (NHL) patients enrolled in NHL‐BFM (Berlin‐Frankfurt‐Muenster) studies. We accessed the seroepidemiological data from 1147 patients that became available during 1990‐2007. We included the records from patients 6 months to 18 years of age with BL, T‐cell lymphoblastic lymphoma (T‐LBL), lymphoblastic precursor B‐cell lymphoma (pB‐LBL), diffuse large B‐cell lymphoma (DLBCL), or anaplastic large cell lymphoma (ALCL). Results: EBV seropositivity was significantly more frequent in patients with BL than in those with T‐LBL. EBV was more prevalent in patients younger than 6 years of age and in patients with BL than in those with non‐BL or T‐LBL. Event‐free survival was significantly lower in varicella‐zoster–seronegative patients, but there was no indication of an association to complications due to varicella zoster infection. We found no associations between herpes simplex virus, varicella zoster virus, or human cytomegalovirus seroprevalence and the pediatric Central European NHL cases. Conclusion: Early EBV exposure may increase the risk of BL in Central Europe. A higher involvement of EBV in European BL than originally reported appears at least probable. Our data support the thesis that the distinction between endemic and sporadic BL is artificial and should be replaced by the differentiation between EBV‐positive and EBV‐negative BL.